Literature Review on the Effectiveness of Transfer Pricing Regulations in Reducing Tax Avoidance in Multinational Corporations - Fandi Ahmad Taufik; Clarissa Prita Aurelia; Icha Aulia Rizka Nugrogo Putri; Muhammad Dirga Sagita; Masiyah Kholmi (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis, Universitas Jenderal Soedirman, Indonesia, 2025)
This research aims to examine the effectiveness of transfer pricing regulations in reducing Tax Avoidance among multinational enterprises. The research utilizes a literature-based approach by reviewing academic studies, policy reports, and international tax governance frameworks such as OECD-BEPS, Country-by-Country Reporting (CbCR), and Automatic Exchange of Information (AEoI). The findings indicate that stringent transfer pricing rules, mandatory documentation, and strengthened audit mechanisms significantly restrict manipulation of intra-group transactions, enhance transparency, and expand the tax revenue base. However, the research also highlights potential unintended effects, including the relocation of business activities to jurisdictions with less strict tax rules if global harmonization effort are weak or inconsistent. The practical implications suggest that governments should align domestic regulations with international standards, develop auditor competencies, improve benchmarking databases, and adopt digital reporting systems to support real-time supervision. For multinational enterprises, compliance with the arm’s length of principle and transparent documentation is crucial in mitigating legal risks and financial penalties. Investors also benefit from improved corporate governance and reduced litigation risk, which strengthen financial stability. The originality of this reserach lies in its comprehensive synthesis of empirical evidence and its policy-oriented recommendations tailored to the current challenges of global taxation.